2021
DOI: 10.1093/carcin/bgab007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary interventions to prevent high-fructose diet–associated worsening of colitis and colitis-associated tumorigenesis in mice

Abstract: Diet is believed to be an important factor in the pathogenesis of Inflammatory Bowel Disease. High consumption of dietary fructose has been shown to exacerbate experimental colitis, an effect mediated through the gut microbiota. This study evaluated whether dietary alterations could attenuate the detrimental effects of a high fructose diet (HFrD) in experimental colitis. First, we determined whether the pro-colitic effects of a HFrD could be reversed by switching mice from a HFrD to a control diet. This diet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Many recent studies have found that HFrD leads to dysbiosis of the gut microbiota, as shown by reduced α-diversity of gut microbiota, reduced probiotics, and enrichment of inflammation-associated bacteria. Montrose et al verified the causative contribution of the microbiota, showing that the worsening effect of fructose on colitis disappeared when gut microbiota was drastically depleted (broad-spectrum antibiotics) or absent (germ-free), which suggested that the gut microbiota was a necessary bridge between HFrD feeding and worsening colitis . It has been observed that the pro-colitis effect of HFrD disappeared and the microbiota was normalized when fructose was removed from the diet . In our study, HFrD feeding altered the structure of the gut microbiota and significantly decreased its richness ( p < 0.01), which is consistent with previous studies. , It is well-known that FL and GOS are poorly absorbed during the gastrointestinal digestion phase, with the majority entering the colon and interplaying with gut microbiota. , Nutrient substrates for the microbiota can regulate the richness and structure of the gut microbiota .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have found that HFrD leads to dysbiosis of the gut microbiota, as shown by reduced α-diversity of gut microbiota, reduced probiotics, and enrichment of inflammation-associated bacteria. Montrose et al verified the causative contribution of the microbiota, showing that the worsening effect of fructose on colitis disappeared when gut microbiota was drastically depleted (broad-spectrum antibiotics) or absent (germ-free), which suggested that the gut microbiota was a necessary bridge between HFrD feeding and worsening colitis . It has been observed that the pro-colitis effect of HFrD disappeared and the microbiota was normalized when fructose was removed from the diet . In our study, HFrD feeding altered the structure of the gut microbiota and significantly decreased its richness ( p < 0.01), which is consistent with previous studies. , It is well-known that FL and GOS are poorly absorbed during the gastrointestinal digestion phase, with the majority entering the colon and interplaying with gut microbiota. , Nutrient substrates for the microbiota can regulate the richness and structure of the gut microbiota .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interventions with dietary supplements may be more effective in mitigating the harmful effects of dietary fructose. , For example, the psyllium improved HFrD-associated worsening of colitis in mice through gut microbial mediation, including a reduction in the abundance of Akkermansia muciniphila enhanced by HFrD feeding. While there are few studies to discuss whether oligosaccharides could relieve high fructose-aggravated colitis …”
Section: Introductionmentioning
confidence: 99%
“…Other applications include exploring the thanatomicrobiome, in determining the time elapsed since microbial death [ 56 ]. Further applications include tracking the microbiome before and after exposure to diseases like SARS COV2 [ 57 ], and determining changes in the microibial composition following dietary alterations [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease or Ulcerative colitis) increase the risk of CRC through long-standing inflammatory states [23]. Nishiguichi et al [24] found procolitic effects of a high fructose diet could be reversed by switching mice to a control diet and thereby prevented a high fructose diet-induced worsening of acute colitis likely from similar mechanisms as mentioned above. Thus, by reducing chronic inflammation of disease states such as IBD, reducing fructose in the diet could be protective against colitis-associated cancers.…”
Section: High Fructose Corn Syrup and Crcmentioning
confidence: 96%